2012
DOI: 10.1208/s12249-012-9859-3
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Artificial Neural Networks for Optimizing Polydispersity Index (PDI) in Nanoprecipitation Process of Acetaminophen in Microfluidic Devices

Abstract: Abstract. Artificial neural networks (ANNs) were used in this study to determine factors that control the polydispersity index (PDI) in an acetaminophen nanosuspension which was prepared using nanoprecipitation in microfluidic devices. The PDI of prepared formulations was measured by dynamic light scattering. Afterwards, the ANNs were applied to model the data. Four independent variables, namely, surfactant concentration, solvent temperature, and flow rate of solvent and antisolvent were considered as input va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…While smaller PDI values indicate the homogeneity of the particle size in suspension. It was reported that PDI lower than 0.2 is considered to be ideal hence, the particle size distribution falls within a narrow range of size (40,(42)(43)(44)(45). The surface charge also plays an important role in the stability of the nanoparticles and the magnitude of zeta potential is indicative of the colloidal stability of the system (46).…”
Section: Insert Figure 2 Herementioning
confidence: 99%
“…While smaller PDI values indicate the homogeneity of the particle size in suspension. It was reported that PDI lower than 0.2 is considered to be ideal hence, the particle size distribution falls within a narrow range of size (40,(42)(43)(44)(45). The surface charge also plays an important role in the stability of the nanoparticles and the magnitude of zeta potential is indicative of the colloidal stability of the system (46).…”
Section: Insert Figure 2 Herementioning
confidence: 99%
“…This caused the precipitation of less drug molecules per nucleation site and consequently decreased PS. 46 Moreover, the decrease in PS with an increased weight of stabilizer could be attributed to the decrease in surface tension, which facilitated the size reduction and stabilized the formed nanoparticles with inhibition of aggregation. 27 It is well known that the conformation of physically adsorbed triblock copolymers (Pluronics) depends on the hydrophobicity of the sorbent surface.…”
Section: Response Surface Plotsmentioning
confidence: 99%
“…Hence, less drug molecules precipitated per nucleation site and a more uniform distribution for the PS was obtained resulting in lower PDI. 46 On the other hand, the increase in molecular weight of stabilizer resulted in an increase in PDI. This could be attributed to the less kinetically restricted adsorption process of the stabilizers onto the drug surfaces that was enabled when the molecular weight of the stabilizer decreased.…”
Section: Response Surface Plotsmentioning
confidence: 99%
“…Also, in this study, polydispersity index (PDI) of nanosuspension samples was determined in the range of 0.09-0.38, which is normal range obtained in microchannel devices and so their good potential to generate the monodispersed colloidal disperses, as reported in the former works (27,28). After considering all findings, a new nanosuspension formulation of stable iodine ( 127 I) was created to achieve minimum particle size.…”
Section: Resultsmentioning
confidence: 79%